2008
DOI: 10.1038/jp.2008.6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of pregnancy exposure to prescription FDA C, D and X drugs in a Canadian population

Abstract: Objective: To examine prescription Food and Drug Administration (FDA) C, D and X drugs in general obstetric population.Study Design: Historical cohort study.Result: A total of 18 575 women who gave a birth in Saskatchewan between January 1997 and December 2000 were included. Among them, 3604 (19.4%) received FDA C, D or X drugs at least once during pregnancy. The pregnancy exposure rates were 15.8, 5.2 and 3.9%, respectively, for category C, D and X drugs, and were 11.2, 7.3 and 8.2%, respectively, in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
18
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
(31 reference statements)
7
18
0
6
Order By: Relevance
“…The majority of analgesic drugs were prescription drugs. This agrees with study done in France[10] and Canada[12] which exhibited that NSAIDs belong to the most common prescription drugs in pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of analgesic drugs were prescription drugs. This agrees with study done in France[10] and Canada[12] which exhibited that NSAIDs belong to the most common prescription drugs in pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Also Wen, Yang, & Krewski, et al . [36] submitted that ginger is a common supplement used for treatment of morning sickness, but there are reports that usage may lead to abortion, mutation of the fetus or increased risk for bleeding. For example, Fischer-Rasmussen, Kjaer, Dahl, et al [37] submitted that ginger has been associated with mutagenesis in a culture of Escherichia coli (E.coli).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Previous study in the USA, Canada and Ireland showed that 4.2-7.8% of pregnant women received potentially teratogenic drugs. 1,[7][8][9][10][11] In the Netherlands, in the period between 1994 and 2003, 1.1% of all drugs received during pregnancy were potentially harmful for the embryo/fetus. 12 In view of the possible impact on public health, it is important to further explore the use of potentially teratogenic drugs among pregnant women in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%